Significant expression of IGFBP2 in breast cancer compared with benign lesions. Issue 4 (24th March 2005) - Busund, L-T; Richardsen, E; Busund, R; Ukkonen, T; Bjørnsen, T; Busch, C; Stalsberg, H
Abstract : Background/Aim: Insulin-like growth factors (IGFs) and IGF binding proteins (IGFBPs) play a role in the normal development of breast tissue, and possibly in breast cancer aetiology. IGFBP2, one of six members of the IGFBP superfamily, acts as regulator of the IGFs and has pleiotropic effects in normal and neoplastic tissues. Because IGFs have mitogenic effects on mammary epithelia, this study investigated IGFBP2 expression in mammary tissues of different benign and malignant entities. Methods: Immunohistochemistry was used to study correlations between the presence and intensity of IGFBP2 staining and tumour type and grade, in addition to steroid hormone receptor status, in 120 breast specimens. Expression was measured by quantitative colour video image analysis and semiquantitative evaluation, and the measurements correlated well ( r = 0.92; p<0.05). Results: Both methods found no significant expression of IGFBP2 in normal glandular cells and hyperplasia (group I). Atypical hyperplasia showed a slightly increased cytoplasmic expression of IGFBP2, and carcinoma in situ showed a distinctive, membrane associated and cytoplasmic expression (group II). Infiltrating carcinomas strongly expressed cytoplasmic IGFBP2 (group III). There were significant differences between group I and II, and between group II and III. There were no significant differences between invasive lobular and invasive ductal carcinoma, or between grades I, II, and III within these entities. There was no significant correlation between IGFBP2 immunostaining and oestrogen or progesterone receptor positivity within the malignant group. Conclusions: IGFBP2 mitogenic signals of autocrine/paracrine regulatory mechanisms may be responsible for the growth of breast carcinomas and IGFBP2 may be an independent indicator of malignancy.